The Effect Soekarno-Hatta - Jakarta Railway Train Project to PT. Kereta Api Indonesia Financial Performance - Nugraha, Adhi; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2013)
Soekarno-Hatta is the largest and busiest airport in Indonesia. So far, the transportation route in and out of the airport is only via the highway road (toll or non-toll) that will pass ring road Jakarta. Currently, the growth of vehicles in Jakarta is very surprising to cause severe traffic jam. The traffic jam that often occured is also affected either directly or indirectly to the traffic conditions and from the Soekarno-Hatta Airport. Indonesia Government through Presidential Decree number 83 of 2011 assigned PT Indonesia Railway to build railway transportation infrastructure through a circular route Jakarta to Soekarno Hatta. The purpose is to develop alternative transportation to help reduce transport problems in the future. For PT KAI itself, as the government-owned company that has a public service obligation (PSO), the project must be done, but there will be a question of whether this project will give positive or negative impact for the company in the future, especially in terms of financial performance. Therefore, to analyze the velua added of this project, the future financial statements between if PT KAI do the project and if they don’t do the project must be compared. As a first step analyzed the financial condition of PT KAI current through the analysis of time series, cross section, a ranking based on two methodologies (BUMN & Moody's), and the current capital structure. Furthermore, the feasibility and demand analysis of the project will be presented as information. To determine how much value the project given, the projected consolidated financial statements and financial statement projections of the project will be conducted. Next step will compare and analyze the results of these projections, which are the consolidated financial statements without a project with projected financial statements consolidation plus project. From the results of the comparison will be observed whether the project also increased ratings of PT KAI. This research provides business solutions to PT KAI to improve financial performance and corporate value by increasing the financial indicators and investment rating. In the end, the project can be roled as a business solution in the future Keywords: Railway Train, Capital Structure, Project Investment, Financial Performance